The Role of Constructivism in the Mathematics Education of Learning Disabled Students. - Johnston, Elizabeth (1994)
Keywords: dept.sed; faculty_collection; sabbatical_report

The road not taken: an integrative theoretical model of reading disability. - Spear-Swerling, L.; Sternberg, R.J. (Journal of learning disabilities, 1994)
This article describes a theoretical model of reading disability that integrates a wide range of research findings in cognitive psychology, reading, and education across the age and grade span. The model shows how reading disability relates to normal reading acquisition, and includes four possible patterns of reading disability: nonalphabetic readers, compensatory readers, nonautomatic readers, and readers delayed in the acquisition of word-recognition skills. We compare our model to the models of other investigators and argue that our model is especially useful to practitioners. Finally, we discuss some of the educational implications of the model.
60 citations (Crossref) [2023-10-31]
Keywords: Adolescent; Adult; Child; Dyslexia; Education; Special; Educational Status; Humans; MLCS; MLOWN; Mental Recall; Phonetics; Verbal Learning; adolescent; adult; child; dept.sed; dyslexia; education; educational status; human; learning; phonetics; psychological aspect; recall; review